An effective passive cell balancing technique for lithium-ion battery - Sudarshan L. Chavan; Manjusha A. Kanawade; Rahul S. Ankushe (Next Energy)
ABSTRACT: The increasing demand for clean transportation has propelled research and development in electric vehicles (EVs), with a crucial focus on enhancing battery technologies. This paper presents a novel approach to a battery management system by implementing a passive cell balancing system for lithium-ion battery packs. The proposed system employs a proportional-integral (PI) controller to address voltage imbalances among individual cells, aiming to improve battery life and longevity without the need for a complex active control circuit. The study explores performance evaluation under diverse conditions, considering factors such as system capacity retention, energy efficiency, and overall reliability. Safety and thermal management considerations play a crucial role in the implementation, ensuring the longevity and stability of the lithium-ion battery pack. The primary objective of this research is to extend the operational life of lithium-ion batteries, reduce maintenance costs associated with battery management, and contribute to sustainable energy solutions. In the presented study, first, a Simulation model is developed in MATLAB, and the results are verified by implementing a hardware model.